Trends in Islamic Microfinance Research: A Bibliometric Analysis Using VOSviewer - Purnomo, Joko Hadi (Institut Agama Islam Al-Fatimah Bojonegoro, 2025)
This study conducts a bibliometric analysis of Islamic microfinance research, utilizing ScienceDirect as the data source and VOSviewer for visualization. A total of 2,826 publications were identified, with a notable surge in research interest over the past decade, culminating in 2024 with the highest number of publications (380). The analysis uncovers key thematic clusters in Islamic microfinance research, including poverty alleviation, entrepreneurship, Sharia compliance, and social impact, emphasizing the multidimensional nature of the field. Network visualizations reveal co-occurrence patterns of keywords, highlighting prominent topics such as “poverty” and “development” or “entrepreneurship” and “financing.” Overlay visualizations identify emerging trends, such as the increasing role of technology and financial innovation in Islamic microfinance. Co-authorship analysis uncovers collaboration patterns, with significant contributions from influential researchers and institutions. Despite advancements, notable gaps persist, particularly in integrating environmental sustainability and addressing regional disparities. This study underscores the evolving role of Islamic microfinance in promoting financial inclusion, ethical financing, and socio-economic development. Future research should adopt interdisciplinary approaches, leverage technological advancements, and address sustainability issues to maximize the global impact of Islamic microfinance